The Impact of Immigration and Customs Enforcement on Immigrant Health: Perceptions of Immigrants in Everett, Massachusetts, USA - Hacker, Karen (2011)
U.S. immigrants have faced a changing landscape with regard to immigration enforcement over the last two decades. Following the passage of the Illegal Immigration Reform and Immigrant Responsibility Act of 1996, and the creation of the Immigration and Customs Enforcement (ICE) agency after the attacks of September 11, 2001, detention and deportation activity increased substantially. As a result, immigrants today are experiencing heightened fear of profiling and deportation. Little research exists on how these activities affect the health and well-being of U.S. immigrant communities. This study sought to address this gap by using community-based participatory research to investigate the impact of enhanced immigration enforcement on immigrant health in Everett, Massachusetts, USA, a city with a large and diverse immigrant population. Community partners and researchers conducted 6 focus groups with 52 immigrant participants (documented and undocumented) in five languages in May 2009. The major themes across the groups included: 1) Fear of deportation, 2) Fear of collaboration between local law enforcement and ICE and perception of arbitrariness on the part of the former and 3) Concerns about not being able to furnish documentation required to apply for insurance and for health care. Documented and undocumented immigrants reported high levels of stress due to deportation fear, which affected their emotional well-being and their access to health services. Recommendations from the focus groups included improving relationships between immigrants and local police, educating immigrants on their rights and responsibilities as residents, and holding sessions to improve civic engagement. Immigration enforcement activities and the resulting deportation fear are contextual factors that undermine trust in community institutions and social capital, with implications for health and effective integration processes. These factors should be considered by any community seeking to improve the integration process.